Children and Violence: Nurturing Social‐Emotional Development to Promote Mental Health. Issue 2 (29th July 2020) - Malti, Tina
Abstract: The absence of violence against children is a fundamental children's right and a major milestone of civilized society. Similarly, reports on incidences of violence by children and youth, including severe cases with devastating consequences, speak to the need that the trauma of exposure to violence in childhood needs to be addressed. While violence and its risk factors are generally understood, what is less clear are the essential protective factors, how we can identify those as early as possible, and how we can use them to prevent and address the trauma of violence exposure in children and youth. In this report, I review pathways of child and youth violence through the lens of social‐emotional development as a central protective factor. Negative emotions of frustration and anger can underlie violence and aggression. Kind emotions, such as caring and our ability to connect with others emotionally, can serve as social‐emotional protective factors. A brief review of the central social‐emotional processes and their development is provided, including the human capacity to feel with others and express empathy, be emotionally aware and care about the effects of one's own actions on others, and be able to regulate the self and their emotions. Given the negative widespread and long‐term impact of exposure to violence, I describe research‐informed attempts to prevent violence exposure across development. Taking a humanistic, strength‐based perspective, the focus is on social‐emotional protective factors to address violence and nurture mental health in every child. I conclude with recommendations for practice and policy.